Analisis Akad Ijarah Tanah Kas Desa Bulusari Kecamatan Gempol Kabupaten Pasuruan dalam Perspektif Fikih Muamalah - Khoiriyah, Siti; Ifdlolul Maghfur; M. Dayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Village cash land is land given to the village government to be managed as one of the village's original sources of income aimed at social interests in village development in improving community welfare. Various ways can be done by the village government to manage village cash land, one of which is through leases. The Bulusari Village Government utilizes village cash land by building shophouses in the Village Market which are then rented to the community. This study aims to determine whether the application of the Bulusari village cash land ijarah contract is in accordance with the principles of muamalah jurisprudence. This research uses field research methods with a qualitative approach because the author goes directly into the field to get information directly from informants. The results showed that the practice of leasing village cash land was in accordance with the principles of muamalah jurisprudence. Aspects such as clarity of the object of the contract (land), rental price agreement, and lease period have been well fulfilled in accordance with Islamic law. The application of ijarah contract on the cash land of Bulusari village helps improve the community's economy, so that the welfare of the community has increased.